2020
DOI: 10.1136/lupus-2020-000387
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting mitochondrial oxidative stress with MitoQ reduces NET formation and kidney disease in lupus-prone MRL-lprmice

Abstract: ObjectivesRecent investigations in humans and mouse models with lupus have revealed evidence of mitochondrial dysfunction and production of mitochondrial reactive oxygen species (mROS) in T cells and neutrophils. This can provoke numerous cellular changes including oxidation of nucleic acids, proteins, lipids and even induction of cell death. We have previously observed that in T cells from patients with lupus, the increased mROS is capable of provoking oligomerisation of mitochondrial antiviral stimulator (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…One of the peculiarities of low-density granulocytes is the increased production of mitochondrial ROS. Recently, it was shown that the mitochondria-targeted antioxidant MitoQ (similar in structure to SkQ1) suppressed NETs accumulation and pathological manifestations in the mouse model of systemic lupus erythematosus [ 102 ].…”
Section: The Role Of Netosis In Host Defence and Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the peculiarities of low-density granulocytes is the increased production of mitochondrial ROS. Recently, it was shown that the mitochondria-targeted antioxidant MitoQ (similar in structure to SkQ1) suppressed NETs accumulation and pathological manifestations in the mouse model of systemic lupus erythematosus [ 102 ].…”
Section: The Role Of Netosis In Host Defence and Pathologymentioning
confidence: 99%
“…In the mouse model of systemic inflammatory syndrome, SkQ1 prevented lethal effect of the inflammatory cytokine TNF [ 111 ]. The antioxidant MitoQ, similar in structure to SkQ1, suppressed NETosis in the mouse model of systemic lupus erythematosus [ 102 ]. These results suggest, that drugs based on mitochondria-targeted antioxidants will be created soon in order to treat diseases associated with the excessive NETosis, and, in particular, to combat COVID-19.…”
Section: Therapy Of Netosismentioning
confidence: 99%
“…Whether SLE-induced NETs are mediated by O 2 •– /H 2 O 2 -independent hyper-citrullination or Nox2-or mitochondria-dependent oxidants remains debatable; however, reports suggest that mitochondria-targeted antioxidants (Mito-Quinone [Mito-Q] and Mito-TEMPOL) attenuated the severity of lupus in the mouse model [ 86 , 87 ]. It was suggested that Mito-Q could inhibit type 1 interferon (IFN-1), upstream of O 2 •– production [ 88 ]. Mito-Q also inhibited IFN-1 that is a byproduct of NETosis [ 88 ].…”
Section: African Americans Are Disproportionately Affected By Inflammmentioning
confidence: 99%
“…It was suggested that Mito-Q could inhibit type 1 interferon (IFN-1), upstream of O 2 •– production [ 88 ]. Mito-Q also inhibited IFN-1 that is a byproduct of NETosis [ 88 ]. Immune system activation by mitochondria was recently reported [ 89 ].…”
Section: African Americans Are Disproportionately Affected By Inflammmentioning
confidence: 99%
See 1 more Smart Citation